Between old and new epistemological paradigms: Gramscian readings of revolutionary processes in Egypt and Tunisia. Issue 6 (2nd November 2021) - Manduchi, Patrizia
ABSTRACT: From a long-term perspective, a Gramscian analytical approach can help us have a better reading of revolutionary processes in MENA countries, expecially if we consider them as the apical moment of a political crisis, originating in the mid-1970s. The most useful Gramscian concepts for this kind of analysis are 'hegemony' and 'civil society', obviously connected with other categories such as 'organic/traditional intellectual' or 'revolution/passive revolution', or even 'modern prince'. Egypt and Tunisia, for their importance in the context of the so called 'Arab Spring' but also because they are the first Arab countries in which Gramsci's knowledge has spread at the beginning of the 1970s, offer very interesting case studies. By comparing by a Gramscian approach some Arab reflections in the 1970s and the ones interpreting 2011 upheavals and their complex and often dramatic consequences, it is possible to demonstrate how a Gramscian analysis can be useful in this ongoing, not yet concluded debate.